SURGICAL MANAGEMENT OF TUBERCULOUS SMALL BOWEL OBSTRUCTION - Akbar, Mohammad; Islam, Fakhar -ul-; Haider, Irfan Zaffar; Naveed, Danish; Akbar, Ismail; Khattak, Irfanuddin; Akbar, Kehkashan; Zafar, Arshad (Journal of Ayub Medical College Abbottabad, 2010)
Background: Acute intestinal obstruction due to tuberculosis is a common surgical problem in our community. Emergency surgery is usually required and surgical procedure depends upon the location and extent of the disease. The aim of this study was to determine the commonly involved region of intestine and different surgical procedures tailored. Methods: Thirty patients operated upon for acute intestinal obstruction in emergency with operative and histopathological findings suggestive of tuberculosis were included in the study. Demographic profile, operative findings, details of surgical procedure, complications and post-op hospital stay were recorded. The patients were followed for 6 months. Results: Intestinal tuberculosis is more common in young female, with male to female ratio of 1:1.5. Stricture of the small bowel was found in 50% of the cases. The next common finding was ileocaecal tuberculosis found in 40% of patients. Strictruplasty was performed in 11 (36.33%). The right hemicolectomy, limited ileocaecal resection and segmental bowel resection with end to end anastomosis were performed in four patients each. Other procedures were release of adhesions and bands in 4 patients, ileotransverse bypass in 1 patient and loop ileiostomy in 2 patients. Major complication in 10 patient and mortality rate was 10%. Conclusion: Because of non-specific clinical features, ignorance and malpractice intestinal tuberculosis presents late. Ileocecal tuberculosis is becoming less common as compared to small bowel strictures. Less radical surgery gives better results. Post operative complications and mortality are related to the perforation of the intestine at the time of surgery. Keywords: intestinal Tuberculosis, Right hemicolectomy, stricturoplasty